A French aristocrat in the American West : the shattered dreams of De Lassus de Luzières - Ekberg, Carl J. (University of Missouri Press, 2010)
Biography of Frenchman who escaped the French Revolution, came to America, and founded the town of New Bourbon, leaving behind extensive commentaries on the Missouri frontier at the close of the colonial era.